Optimizing BPJS Referral Systems: A Pathway to Equitable, Sustainable Healthcare in Indonesia - Damayanti, Nabila Ardelia; Putri, Dealonika Amanda; Napitupulu, Gladys Shevani Chilau; Kholvi, Indy Zaheera; Khairunnisa, Khairunnisa; Mustama'ah, Nadiyatus Sholatil; Rachmad, Rayhan Ramadhan Daffa Attariansyah; Putri, Serli Kusuma Dewi Dwi; Turmudi, Syifa Rabitha Alizza; Santi, Neni Fidya; Evi, Nurul (Tarqabin Nusantara Group, 2025)
The BPJS referral system in Indonesia has been instrumental in expanding healthcare access, yet challenges such as unnecessary referrals, governance transparency, and cost inefficiencies persist. Strengthening primary healthcare infrastructure, enhancing quality control, and improving patient education are critical to optimizing the system's effectiveness. This study explores the impact of targeted interventions on BPJS referral accessibility. This study employed a systematic review approach guided by the PRISMA framework. Peer-reviewed studies published between 2019 and 2023 were identified through databases such as PubMed, Scopus, and Web of Science using terms like